Oedipus Complex In Lawrence’S Sons and Lovers: The Influence of the Mother-Son Relationship in D.H. Lawrence's Autobiographical Novel (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Sons and Lovers is D.H.Lawrence’s autobiographical novel, which amply enlightens us to Lawrence’sviews regarding dynamics of self and society and various dimensions of relations that exist in context of an individual’s social interaction. Hedescribed his own subject matter as “the relation between men and women….”(Boris Ford, 282), this novel as the name suggests, deals withsomething which was quite untalked of in novels. It revolves mostly around therelationship between Paul Morel and his mother, the influence of mother’sexcessive hold on her son’s life and the efforts of the son to free him fromthe crippling of mother’s hold. The novelist emphasis the excessive influenceof the mother’s views on the son’s life by basing the son’s relation withmother on Freud’s theory of Oedipus Complex. Paul Morel is the depiction ofD.H. Lawrence himself.